A Reform in Search of a Purpose: French Insolvency Law Changes (Again!). Issue 3 (15th October 2014) - Omar, Paul J.
Abstract This article charts the additions made by the French legislator to the insolvency framework, reformed relatively recently in 2005 and 2008, consisting in a fresh set of amendments in 2014 aimed at encouraging more take up of upstream rescue proceedings as well as improving the existing procedures.